THE RELATIONS AMONG LEARNING MOTIVATION, REASONING ABILITY, AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOMES ON STUDENT IN GRADE VIII - Nurul Amalina Kurniasih; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The result of the study in a low student is related to many factors. Learning motivation, reasoning ability, and learning environment at home are estimated to have a relationship between learning outcomes. This research aims to know there is or not a positive relationship between learning motivation, reasoning ability, and learning environment at home with mathematics learning outcomes on students in grade VIII of Muhammadiyah Junior High School 7 Yogyakarta (SMP Muhammadiyah 7 Yogyakarta) in odd semester academic year 2017/2018. The population in this research are all students in grade VIII of SMP Muhammadiyah 7 Yogyakarta in odd semester 2016/2017 academic year as many as seven classes. Sampling technique using sampling random technique to class and class VIII G is chosen as the sample class. The data collecting technique using questionnaires and test methods. The instrument of collecting data using questionnaires of motivation to learn, a test of reasoning ability, and a questionnaire of the learning environment at home and mathematics test. Data analysis to hypotheses testing using correlation analysis product-moment and double linear regression analysis. The result of this research shows that if there is a positive relationship between learning motivation, reasoning ability, and learning environment at home with mathematics learning outcomes. Insignificance level 5%, =3, =23, Fcount = 23,6772 and Ftable = 3,0280, Fcount > Ftable with double correlation coefficient R = 0,8691 and double three-variable regression similarity namely Â Big relative contribution , , , with double determination coeffition 0,7266 and efective contribution , Â dan